2011
DOI: 10.1111/j.1532-7795.2011.00762.x
|View full text |Cite|
|
Sign up to set email alerts
|

Attachment Style, Vagal Tone, and Empathy During Mother–Adolescent Interactions

Abstract: We tested associations among empathic responsiveness, attachment style, and vagal tone (a physiologic index of emotion regulation) in 103 mother–adolescent dyads. Dyads discussed positive and negative topics and then separately reviewed a videotape of the interaction and rated their own and the other person's affect at one‐minute intervals. We used multilevel modeling to analyze the association between one's rating of the other person's affect and the other person's affect (empathic sensitivity), and the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 108 publications
0
54
0
Order By: Relevance
“…Conversely, adult attachment insecurity (particularly avoidance) is associated with lower levels of empathy (Joireman, Lasane, Bennett, Richards, & Solaimani, 2001;Wei, Liao, Ku, & Shaffer, 2011). Among adolescents, attachment security is associated with greater empathy and vagal tone during interactions with their mothers (Diamond, Fagundes, & Butterworth, 2012). In experimental research, contextual priming of attachment security has been shown to strengthen empathic responding and inhibit personal distress, providing evidence for a causal link between secure states of mind and empathy among adults (Mikulincer et al, 2001).…”
Section: Empathy and Attachmentmentioning
confidence: 97%
“…Conversely, adult attachment insecurity (particularly avoidance) is associated with lower levels of empathy (Joireman, Lasane, Bennett, Richards, & Solaimani, 2001;Wei, Liao, Ku, & Shaffer, 2011). Among adolescents, attachment security is associated with greater empathy and vagal tone during interactions with their mothers (Diamond, Fagundes, & Butterworth, 2012). In experimental research, contextual priming of attachment security has been shown to strengthen empathic responding and inhibit personal distress, providing evidence for a causal link between secure states of mind and empathy among adults (Mikulincer et al, 2001).…”
Section: Empathy and Attachmentmentioning
confidence: 97%
“…Securely attached individuals generally see other people as reliable sources of support, whereas insecurely attached individuals see others as unreliable sources of potential pain (e.g., Dykas and Cassidy, 2011). And although attachment security has been generally associated with the production of empathic behaviors across the lifespan (Mikulincer et al, 2001; Mikulincer and Shaver, 2005; Mikulincer et al, 2005; Diamond et al, 2012), it is possible that it does not affect the ability to represent all three varieties of negative states equally (Johnson et al, 2013). …”
Section: Prosocial Behavior As Helping Sharing and Comforting Subtypesmentioning
confidence: 99%
“…Heart-rate deceleration has been shown to occur in contexts that evoke a sympathetic/compassionate response, whereas heart-rate acceleration occurs in contexts that evoke distress (see Eisenberg et al, 2006; Goetz et al, 2010). Moreover, researchers have sometimes found that higher levels of baseline RSA (or heart-rate variability) were associated with higher levels of empathy or sympathy (Diamond, Fagundes, & Butterworth, 2012; Liew et al, 2011), low personal distress (Fabes, Eisenberg, & Eisenbud, 1993), and prosocial behavior (Fabes, Eisenberg, Karbon, Troyer, & Switzer, 1994). However, other researchers have not found support, or have found mixed support, for these relations (Graziano, Keane, & Calkins, 2007; Hastings, Zahn-Waxler, Robinson, Usher, & Bridges, 2000; Zahn-Waxler, Cole, Welsh, & Fox, 1995).…”
Section: Antecedents To Children’s Sympathymentioning
confidence: 99%
“…Of note, few existing studies are longitudinal, and nearly all studies measured sympathy/empathy in toddlers/preschoolers and/or kindergartners to second graders. To our knowledge, only Diamond et al (2012) and Hastings et al (2000) measured outcomes primarily for children aged 6 to 7 years or older. Perhaps RSA functioning has more positive relations with sympathy in older children because of stronger positive relations with variables such as regulation.…”
Section: Antecedents To Children’s Sympathymentioning
confidence: 99%